2006
DOI: 10.1080/14733280601005617
|View full text |Cite
|
Sign up to set email alerts
|

‘Playtime in the Borderlands’: Children's Representations of School, Gender and Bullying through Photographs and Interviews

Abstract: Photography has been commonly used as a research tool in studies of childhood/children. However images of school children in official documentation are rarely taken or chosen by children and may not reflect their real experiences. This research considered the photographs taken by year six primary school children of their school and the images they chose to represent themselves. Subsequent interviews with children revealed attitudes to school, the importance of playground relationships in the construction of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 28 publications
(22 reference statements)
0
62
1
Order By: Relevance
“…This would be to neglect the established literature that, since the 1990s, has demonstrated the importance of recognising the competencies and capacities of children and young people as individual social actors who make sense of, and actively engage with, their social worlds (e.g. James and James, 2004;James and Prout 1997;James et al, 1998;Holloway and Valentine, 2000;Hutchby and Moran-Ellis 1998;Newman et al 2006;Smith and Barker, 2001;Valentine, 1996). As with other social actors, children and young people's agency is seen to arise from their structural and ideological position in society (Matthews and Limb 1999 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would be to neglect the established literature that, since the 1990s, has demonstrated the importance of recognising the competencies and capacities of children and young people as individual social actors who make sense of, and actively engage with, their social worlds (e.g. James and James, 2004;James and Prout 1997;James et al, 1998;Holloway and Valentine, 2000;Hutchby and Moran-Ellis 1998;Newman et al 2006;Smith and Barker, 2001;Valentine, 1996). As with other social actors, children and young people's agency is seen to arise from their structural and ideological position in society (Matthews and Limb 1999 …”
Section: Discussionmentioning
confidence: 99%
“…The children were then asked to represent their 'flood journey' in a storyboard. Storyboards have been shown to be an effective method in children's research because they avoid problems associated with low literacy levels and give participants the freedom to 'represent' themselves in particular ways (Newman et al 2006;Hemming 2008;Ansell and van Blerk 2004;Smith and Barker 2001). We then conducted one-to-one interviews with the children (15-20 minutes, 42 recorded in total -25 primary and 17 secondary pupils) using the storyboards as prompts (Walker et al 2009;Loizos 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo elicitation, or PhotoVoice, is a research technique which has been identified as a child--focussed, flexible approach to research that allows children's views to be communicated on their own terms in the research process (Darbyshire, MacDougall, & Schiller, 2005;Newman, Woodcock, Dunham, 2006;Due, et al, 2014). Photo elicitation involves participants being provided with a camera (in this case, a digital camera) and This is an Author's Accepted Manuscript of a paper published in the Educational and Developmental Psychologist Copyright Cambridge University Press DOI: 10.1017/edp.2016.9 asked to take photos according to a particular theme that relates to the research aims.…”
Section: Participantsmentioning
confidence: 99%
“…The use of photos and the process of taking them are supposed to be amusing for children (Cook & Hess, 2007). Thus, photo interviews are regarded as a method that may increase children's interest in participating in a study, intensify their engagement with a scientific research project, and maintain their interest throughout the research process (Cappello, 2005;Clark-Ibáñez, 2007;Croghan et al, 2008;Einarsdóttir, 2005;Harper, 2002;Newman, Woodcock, & Dunham, 2006;White et al, 2010).…”
Section: Photo Interviews In Research With Childrenmentioning
confidence: 99%